Electrochemical Potentiostatic Activation for the Improvement of 270 nm AlGaN-Based UV-C Light-Emitting Diodes. (1st February 2022) - Lee, Koh Eun; Choi, Rak Jun; Kang, Hyunwoong; Shim, Jong In; Ryu, Sang-Wan; Cho, Jaehee; Lee, June Key
Abstract : The electrochemical potentiostatic activation (EPA) method was performed by removing hydrogen atoms from the inside of the Mg-doped p -GaN/ p -AlGaN multilayer of 270 nm AlGaN-based UV-C light-emitting diodes (UV-C LEDs). The EPA evaluation was controlled among the applied voltages of 2, 3, and 4 V for 10 min under 1.0 M HCl solution, and the hole concentration inside the p -GaN/ p -AlGaN multilayer was decreased. To evaluate the characteristics and reliability of UV-C LEDs, the basic flip chip process was applied and then mounted on the AlN ceramic package by AuSn eutectic bonding. Compared to the as-fabricated LED, we demonstrated an increase of over 8% in light output power at 350 mA in UV-C LEDs by improving internal quantum efficiency (IQE) with EPA treatment at 3 V. The enhanced IQE and higher EQE contributed to improving the reliability of the LEDs, thus resulting in a ∼7% lifetime extension.